Progress of malignant mesothelioma research in basic science: A review of the 14th international conference of the international mesothelioma interest group (iMig2018). (January 2019) - Wu, Licun; Dell'Anno, Irene; Lapidot, Moshe; Sekido, Yoshitaka; Chan, Mei-Lin; Kohno, Mikihiro; Serre-Beinier, Veronique; Felley-Bosco, Emanuela; de Perrot, Marc
Highlights: Progress of mesothelioma research in basic science at the 14th iMig2018. Molecular pathogenesis and perspectives on potential therapeutics. Inhibiting YAP/TAZ, heparanase, RAN, MIF/CD74 and GITRL-GITR signaling. Targeting mesothelioma stem cells by modulating tumor microenvironment. Abstract: Here we summarize the most recent update of mesothelioma research in basic science presented at the 14 th iMig2018 international conference. The symposium of basic science track mainly focused on the drivers of mesothelioma initiation and progression, molecular pathogenesis, and perspectives on potential therapeutic approaches. This review covers several promising fields including strategies efficiently inhibiting YAP/TAZ functions or their critical downstream targets, heparanase inhibitors, RAN depletion, and MIF/CD74 inhibitors that may be developed as novel therapeutic approaches. In addition, targeting mesothelioma stem cells by depleting M2-polarized macrophages in tumor microenvironment or blocking Tnfsf18 (GITRL)-GITR signalling might be translated into therapeutic modalities in mesothelioma treatment.